A Case Study: Student’s Anxiety in Learning English at the 7th Grade of SMP Negeri 3 Muara Bungo - Fatmawati Fatmawati (Universitas Muhammadiyah Muara Bungo, 2021)
This study was carried out to investigate foreign language anxiety of EFL junior secondary school students at the 7th grade of SMPN 3 Muara Bungo. Specifically, it sought to identify what factors that may contribute to anxiety in English learning environment based on the students’ perspectives. The method was used in this study was qualitative method with case study approach. Fifteen anxious students were selected as the participants. The data were gathered through structured interviews and classroom observations. The result of the study showed that speaking in front of the class, being laughed at by others, incomprehensible input, students’ beliefs about language learning, teacher personality, and lack of preparation were the six factors that may contribute to the students’ anxiety in learning English.